Avoided land use conversions and carbon loss from conservation purchases in California. Issue 4 (4th July 2018) - Moanga, Diana; Schroeter, Isabel; Ackerly, David; Butsic, Van
ABSTRACT: Conversion of natural lands to residential and agricultural uses can limit carbon (C) storage. Conservation measures, such as purchasing land to prevent development, can preserve stored aboveground C. However, since it is difficult to know what would happen to the land in the absence of conservation interventions, the additional carbon benefit of these programs remains unknown. Therefore, we analyzed 73 coastal parcels (292, 184 total acres) acquired by the California State Coastal Conservancy (SCC) and developed counterfactual scenarios to highlight the impact of conservation actions. We found that an additional 55 * 10 3 Mg aboveground C (1.357% of the total stored carbon) was protected. The methodology we develop here, which incorporates expert opinion and neighboring land conversion trends, effectively evaluates the impact of conservation purchases to prevent land conversion, and could be used to measure changes of various ecosystem services.